A new Ovia species (Araneae, Lycosidae) from Singapore, with the transfer of Pardosa alboannulata Yin et al., 1997 - Lu, Tian; Koh, Joseph K. H.; Zhang, Zhi-Sheng; Li, Shuqiang (Zootaxa, 2018)
A new species of wolf spiders, Ovia macritchie sp. nov., is discovered in Singapore. It is closely related to O. procurva (Yu & Song, 1988), hitherto the only species of Ovia Sankaran, Malamel & Sebastian, 2017. O. macritchie also resembles Pardosa alboannulata Yin et al., 1997 from China, which is herein transferred to Ovia. All of them share a uniquely hooked terminal apophysis on the male pedipalp. Colour photos, line drawings, SEM photos and detailed descriptions are provided for both the new species O. macritchie and the newly combined species O. alboannulata.